Lipophilic Resazurin in Bioelectrochemical Systems: Role in Regulating Carbon Metabolic Pathways - Siyu Tan; Xiao Zhu; Xinxin Wang; Huangsheng Su; Zongqiang Zhu; Xiaobo Luo; John R. Reinfelder; Yundang Wu; Fangbai Li (ChemElectroChem)
Lipophilic electron shuttles (ESs), such as phenazine and phenoxazine, can penetrate the outer membrane and enter the periplasmic space, mediating extracellular electron transfer reactions. This study investigates how lipophilic ESs (resazurin, a phenoxazine) regulate carbon metabolic pathways in bioelectrochemical systems using Shewanella oneidensis MR‐1 as a model organism. Through the analysis of acetate yield, CO2 production, coulombic efficiency, and other parameters, it is found that resazurin increases coulombic efficiency (26% vs 17% for anthraquinone‐2,6‐disulfonic acid [AQDS]) and reduces acetate yield (82% vs 90% for AQDS) while slightly increasing CO2 production (13.1% vs 11.8% for AQDS), indicating a shift in carbon metabolism. Transcriptome analysis reveals significant upregulation of genes involved in the NADH‐dependent metabolic pathway (e.g., nuoHIJKLMN) and ATP synthesis (atpABDEFGH) under resazurin conditions. Mutant strains lacking key genes in oxidative phosphorylation (Δatp) or substrate‐level phosphorylation (Δack&pta) further confirm the regulatory role of lipophilic shuttles. The study proposes that lipophilic ESs penetrate the periplasm, altering the redox state of inner‐membrane quinones and activating the NADH‐dependent metabolic pathway via the Arc system. This mechanism enhances TCA cycle activity and overall lactate metabolic efficiency. The findings provide insights into microbial carbon metabolic regulation and offer strategies for optimizing bioelectrochemical systems for bioremediation.